2021
DOI: 10.31234/osf.io/s3hr6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social Rejection Sensitivity and its Role in Adolescent Emotional Disorder Symptomatology

Abstract: Many socio-emotional disorders first emerge during adolescence, a time characterized by development in social functioning. Social risk factors, such as social rejection sensitivity (SRS), then, may be promising targets for intervention. To explore this, 362 participants (M (SD) age=19.66 (4.8), 63% female) completed a novel social interpretation bias modification task, the ambiguous social scenarios task (ASST). Supporting the importance of SRS in the experience of socio-emotional disorders, SRS partially acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…However, meta-analytic evidence provides no support for gender differences in the association between social rejection sensitivity and mental health (i.e., depression symptoms; Gao et al, 2017). Similarly, a previous study in a sample of participants with high ethnic, socioeconomic and gender diversity showed that the impact of these demographic variables did not moderate the impact of social rejection sensitivity on mental health (Minihan et al, 2021). While we included self-identified gender and ethnicity as covariates in all analyses, the lack of representativeness of our sample (i.e., majority White and female) limits the conclusions we can draw about the impact of these demographic variables on mental health trajectories.…”
Section: Discussionmentioning
confidence: 90%
“…However, meta-analytic evidence provides no support for gender differences in the association between social rejection sensitivity and mental health (i.e., depression symptoms; Gao et al, 2017). Similarly, a previous study in a sample of participants with high ethnic, socioeconomic and gender diversity showed that the impact of these demographic variables did not moderate the impact of social rejection sensitivity on mental health (Minihan et al, 2021). While we included self-identified gender and ethnicity as covariates in all analyses, the lack of representativeness of our sample (i.e., majority White and female) limits the conclusions we can draw about the impact of these demographic variables on mental health trajectories.…”
Section: Discussionmentioning
confidence: 90%
“…However, meta-analytic evidence provides no support for gender differences in the association between social rejection sensitivity and mental health (i.e., depression symptoms; Gao et al, 2017). Similarly, a previous study in a sample of participants with high ethnic, socioeconomic and gender diversity showed that the impact of these demographic variables did not moderate the impact of social rejection sensitivity on mental health (Minihan et al, 2021). Another limitation of the current study was that we did not include a direct measure of physical distancing at each timepoint.…”
Section: Discussionmentioning
confidence: 90%